Sophora flavescens-Astragalus mongholicus herb pair in the progression of hepatitis, cirrhosis, and hepatocellular carcinoma: a possible mechanisms and relevant therapeutic substances - Yang, Xiao; Liang, Chen; Shao, Li; Cui, Wenxuan; Ning, Ruobing; Ke, Fan; Wang, Yue; Gao, Peng; Yin, Yidi; Li, Qing (Frontiers in Pharmacology, 2024)
Background: Both Sophora flavescens (SF) and Astragalus mongholicus (AM) are known for their anti-inflammatory, antifibrotic, and anticancer activities. However, the efficacy, multi-target mechanisms, and therapeutic substances of SF-AM herb pair on the progression of hepatitis-cirrhosishepatocellular carcinoma (HCC) remain unclear.To investigate the efficacy, mechanisms, and potential therapeutic substances of SF-AM herb pair in the progression of hepatitis-cirrhosis-HCC.Methods: Firstly, diethylnitrosamine was used to establish the hepatitis-cirrhosis-HCC model. HE staining and non-targeted metabolomics were used to evaluate the efficacy of SF-AM herb pair. Subsequently, the absorbed components of SF-AM herb pair in the plasma of rats were determined through HPLC-Q-TOF-MS/MS analysis. Flow cytometry, western blot, and qRT-PCR were then employed to assess CD4 + and CD8 + T lymphocytes, PI3K/Akt signaling pathway-related proteins, and their corresponding mRNAs. Simultaneously, the efficacy and mechanism of SF-AM herb pair on HCC were confirmed by in vitro experiments. Finally, Pearson correlation analysis was performed between pharmacodynamic indicators and in vivo components to identify the potential therapeutic substances of SF-AM herb pair.Results: SF-AM herb pair can alleviate the pathological damage and reverse metabolic abnormalities in hepatitis, cirrhosis, and HCC rats, particularly during the hepatitis and cirrhosis stages. Pharmacological researches have demonstrated that SF-AM herb pair can increase the proportion of CD8 + T lymphocytes, inhibit the expression of PI3K, Akt, p-Akt, NF-κB p65, NF-κB pp65, and Bcl-2, as well as increase the expression of IκBα, Bax, and cleaved caspase-3. These findings suggest that SF-AM herb pair has the ability to enhance immunity, anti-inflammation and promote apoptosis. Cell experiments have shown that SF-AM herb pair can inhibit the proliferation of HepG2 cell and regulate the PI3K/Akt signaling pathway. Moreover, 23 absorbed prototypical components and 53 metabolites of SF-AM herb pair were identified at different stages of HCC rats. Pearson correlation analysis revealed that matrine, cytisine, wogonoside, and isoastragaloside are potential therapeutic substances in SF-AM herb pair for the prevention and treatment of hepatitis, cirrhosis, and HCC.In summary, this study revealed the efficacy, mechanisms, and potential therapeutic substances of SF-AM herb pair in the hepatitis-cirrhosis-HCC axis and provided a reference for its clinical application.